Overview of medical waste management in RSUD Kabupaten Kediri. Script. Faculty of Society’s Health - Ukik Agustina; Yuliani; Ema Mayasari; Arina Chusnatayaini (Universitas STRADA Indonesia, 2022)
The Kediri Regency General Hospital is a health institution that has many installations and is never separated from the generation of medical waste. The impact of less than optimal waste management from the time the waste is produced to final disposal is very detrimental to public health and can reduce environmental quality and cause health problems, pollution of air, soil and water, and low aesthetic value. This study aims to determine the Medical Waste Management System in the Emergency Installation of the Kediri Regency General Hospital based on the Minister of Health Regulation Number 7 of 2019.This research was conducted in the Emergency Installation of the Regional General Hospital of Kediri Regency. This study used descriptive qualitative method. The study was conducted in April 2022 at the Emergency Installation of the Kediri Regency General Hospital. The research sample is 6 people. Research variables are Sorting, Storage, Transportation, Temporary Shelter, Destruction. The research instrument is the researcher, interview guide, checklist sheet, and documentation. Data analysis using three main activity lines, namely data reduction, data presentation, and drawing conclusions.The results showed that the management of medical solid waste starting from the stages of sorting, storing, transporting, Temporary Shelter and Destruction at the Kediri Regency General Hospital was in accordance with the requirements of the Indonesian Minister of Health Regulation No. 7 of 2019. It is recommended to the Kediri Regency Regional General Hospital. carry out routine socialization related to medical waste management SOPs, monitor and evaluate medical waste bins, transport should use special routes, as well as monitor and evaluate the safety of Temporary Shelters.